Leviathan Antropofágico: thinking the state from Latin American perspectives (Simbiótica. Revista Eletrônica, 2016)
This article briefly outlines a historical trajectory that formed the state, creating a system and political structure exported to the rest of the world. Here we do a literature review of some researchers trying to create a Latin American thought in social and political theory in the face of Eurocentric arrays. We aim to bring different approaches and concepts that have in common the defense to think critically the social science from the global south reality. Finally, we advocate an autonomous Latin American academy, but that does not deny all knowledge production arising from the global north.Keywords: State; civil society; Latin American Thought; knowledge.